2007
DOI: 10.1038/nsmb1239
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of HDAC complexes in promoter silencing, antisense suppression and DNA damage protection

Abstract: Histone acetylation is important in regulating DNA accessibility. Multifunctional Sin3 proteins bind histone deacetylases (HDACs) to assemble silencing complexes that selectively target chromatin. We show that, in fission yeast, an essential HDAC, Clr6, exists in two distinct Sin3 core complexes. Complex I contains an essential Sin3 homolog, Pst1, and other factors, and predominantly targets gene promoters. Complex II contains a nonessential Sin3 homolog, Pst2, and several conserved proteins. It preferentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
246
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(266 citation statements)
references
References 60 publications
17
246
2
1
Order By: Relevance
“…This further supports the notion that HDAC inhibition stabilizes DSBs and/or increases DNA sensitivity to DSBs. In fission yeast, strains mutated for components of HDAC complexes are highly sensitive to genotoxic agents, with a massive accumulation of DSBs [53]. The same study also demonstrated that these strains increase antisense transcripts, suggesting that DSBs could be triggered by the presence of RNA-DNA hybrids, structures known to induce genomic instability [54].…”
Section: Sensitization To Exogenous Dna Damage By Hdacimentioning
confidence: 48%
“…This further supports the notion that HDAC inhibition stabilizes DSBs and/or increases DNA sensitivity to DSBs. In fission yeast, strains mutated for components of HDAC complexes are highly sensitive to genotoxic agents, with a massive accumulation of DSBs [53]. The same study also demonstrated that these strains increase antisense transcripts, suggesting that DSBs could be triggered by the presence of RNA-DNA hybrids, structures known to induce genomic instability [54].…”
Section: Sensitization To Exogenous Dna Damage By Hdacimentioning
confidence: 48%
“…Furthermore, mRNAs are asymmetrically partitioned on centrosomes during mollusk embryonic cleavages (Lambert and Nagy, 2002). Finally, SpRrp6 and SpDis3 processes or degrade centromeric siRNAs that regulate kinetochore function (Murakami et al, 2007;Nicolas et al, 2007); whether these RNAs underlie the mechanism of metazoan Rrp6 action on mitotic chromosomes is unknown.…”
Section: Models For Rrp6 Function In Cell Cycle Progressionmentioning
confidence: 99%
“…The only core subunit linked to these phenomena is Csl4 (Baker et al, 1998) and that effect has been shown to be indirect (van Hoof et al, 2000). It has been suggested that the mitotic function of SpRrp6 and SpDis3 is to process or degrade centromere-associated small inhibitory RNAs (siRNAs; Buhler et al, 2007;Murakami et al, 2007;Nicolas et al, 2007). Whether these results in S. pombe explain the mitotic phenotypes associated with perturbation of Rrp6 and Dis3 in other eukaryotes is unknown.…”
mentioning
confidence: 99%
“…The HDACs Clr3 (a component of the SHREC (Snf2/Hdaccontaining repressor complex) silencing complex 23 ) and Clr6 (which exists in multi-subunit complexes 21 ) have been implicated in controlling Tf2 expression in S. pombe 10,21,23 . We investigated potential genetic interactions between HDACs and Abp1 in Tf2 silencing.…”
Section: Abp1 Recruits Hdacs To Tf2 and A Heterochromatic Locusmentioning
confidence: 99%
“…CENP-Bs bind to Tf2 retrotransposons and their remnants, and mediate Tf2 silencing by recruiting the class I histone deacetylase (HDAC) Clr6 (refs 21,22) and the class II HDAC Clr3 (ref. 23).…”
mentioning
confidence: 99%